Why young elite athletes fear failure: Consequences of failure - Sagar, S. S.; Lavalle, D.; Spray, C. M. (Journal of Sports Sciences, 2007)
Fear of failure can have negative effects on children in achievement settings, affecting many aspects of their lives. Perceiving the consequences of failure to be aversive provides the basis for fear of failure, and the anticipation of a threatening outcome elicits fear. Problems attributed to fear of failure in achievement settings are prevalent. Sport is a popular and significant achievement domain for children and adolescents and there is a lack of research on fear of failure in sport among this age group. Therefore, the aim of the present study was to investigate fear of failure in the sport domain among young elite athletes, and to explore their perceptions of the consequences of failure. Interviews were conducted individually with nine athletes aged 14 - 17 years (5 males, 4 females). Analysis identified and organized perceived consequences of failure into themes and categories. Results revealed that the most commonly perceived aversive consequences of failure were diminished perception of self, no sense of achievement, and the emotional cost of failure. These findings are consistent with those reported in adult population, suggesting the potential for generalizing existing results to young elite athletes.